Integrated 16s RNA sequencing and network pharmacology to explore the effects of polyphenol-rich raspberry leaf extract on weight control - Wang, Tao; Yang, Jing; Huang, Ziang; Wang, Fei; Liu, Ruzi; Liu, Yongping; Li, Xiaojun (Frontiers in Nutrition, 2024)
Introduction Obesity is recognized as a chronic low-grade inflammation associated with intestinal flora imbalance, leading to dyslipidemia and inflammation. Modern research has found that polyphenols have anti-obesity effects. However, the mechanism of action of raspberry leaf extract (RLE) with high polyphenols in regulating obesity is still unknown. This study investigated the improvement effect of supplementing RLE on high-fat diet (HFD) induced obesity in mice. Methods RLE was used to intervene in HFD induced C57BL/6J male mice during prevention stage (1-16 weeks) and treatment stage (17-20 weeks). Their weight changes and obesity-related biochemical indicators were measured. The changes in intestinal flora were analyzed using 16S rRNA sequencing, and finally the targets and pathways of the 7 typical polyphenols (quercetin-3-O-glucuronide, ellagic acid, kaempferol-3-O-rutinoside, chlorogenic acid, brevifolin carboxylic acid, quercetin-3-O-rutinoside, and quercetin) of RLE in the regulation of obesity were predicted by network pharmacology approach. Results and discussion The results showed that RLE effectively prevented and treated weight gain in obese mice induced by HFD, alleviated adipocyte hypertrophy, reduced Interleukin-6 and Tumor Necrosis Factor Alpha levels, and improved intestinal flora, especially Muriaculaceae, Alistipes and Alloprevotella, and decreased the Firmicutes/Bacteroidota ratio. Network pharmacology analysis selected 60 common targets for 7 RLE polyphenols and obesity. Combined with protein-protein interaction network, enrichment analysis and experimental results, TNF, IL-6, AKT1, and PPAR were predicted as potential key targets for RLE polyphenols. Conclusion The potential mechanism by which polyphenol-rich RLE regulates obesity may be attributed to the specific polyphenols of RLE and their synergistic effects, therefore RLE has a great anti-obesity potential and may be used as a means to alleviate obesity and related diseases.